Creating an Effective Multilingual Learning Curriculum for Bilingual Students in Indonesia, Fostering Language Proficiency - Sari, Septy Kumala; Mustofa, S. Ahmad Marjuki; Pradana, Dian Arief (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This journal explores the development of a curriculum designed for effective multilingual learning specifically catering for bilingual students in Indonesia. As the country embraces linguistic diversity, the need for a curriculum that accommodates multiple languages becomes essential to foster inclusivity and improve educational outcomes. This study investigates current educational practices, identifies challenges faced by bilingual learners, and proposes a comprehensive framework that integrates cultural relevance and language proficiency. Using qualitative and quantitative research methods, including surveys and interviews with educators and students, the findings highlight the importance of contextualised learning experiences and teacher training. The proposed curriculum aims to enhance cognitive development, cultural awareness and linguistic skills among bilingual students, ultimately contributing to a more equitable education system in Indonesia. This research underscores the need to adapt educational approaches to meet the needs of diverse language communities, thus supporting national development goals in the context of globalisation.